Voice disorders in teachers. Implications for occupational health nursing care - Marta Regina Cezar-Vaz (Investigación y Educación en Enfermería, 2013)
Objective. To identify the occupational characteristics and their implications for the occurrence of voice disorders among teachers in early childhood and primary education. Methodology. A quantitative and exploratory research was undertaken in a metropolitan city of the state capital of Rio Grande do Sul/Brazil. The sample consisted of 37 teachers from early childhood and primary education. Results. All participants were female, with a mean age of 40 years. Seventy-eight percent indicated one or more voice disorders (54% hoarseness, 41% voice cracks, 27% voice loss and 3% coughing). The noisy school environment was identified as a possible triggering factor of the voice disorder in 49% of cases. Forty-six percent of all teachers indicated not doing any treatment in case of voice disorders. The most frequently used specific measures were: medication use (32%) and speech therapy (5%). Conclusion. Voice disorders are frequent among the participating teachers and are mainly related to a noisy school environment. It is important for the nurse to intervene, using educative strategies to reduce the risk factors for the vocal health of teachers working in these conditions.